Uji Aktivitas Antioksidan Dan Toksisitas Akut Kombinasi Ekstrak Biji Kebiul (Caesalpinia Bonduc (L.) Roxb) Dan Bajakah Jie Xue Teng (Spatholobus Suberectus Dunn) Serta Formulasi Kapsul - Yohana Laura Silfia Pora; Sapto Yuliani; Nurfina Aznam; Sri Mulyaningsih (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Oxidative stress plays a major role in the pathogenesis of various degenerative diseases, necessitating effective and safe sources of natural antioxidants. The plants kebiul (Caesalpinia bonduc (L.) Roxb.) and bajakah jie xue teng (Spatholobus suberectus Dunn) are known to possess antioxidant potential; however, the activity of their combination has not been extensively reported. Objective: This study aimed to evaluate the antioxidant activity, acute toxicity, and capsule formulation of a combination of 70% ethanol extracts of kebiul seeds and bajakah jie xue teng. Methods: Extraction was performed by maceration using 70% ethanol. Total phenolic content was determined using the Folin–Ciocalteu method, while antioxidant activity was assayed using the DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging method. Extract combinations at ratios of 1:1, 1:3, and 3:1 were tested to obtain the lowest IC₅₀ value. An acute toxicity test was conducted on female Swiss mice following the OECD 423 (Acute Toxic Class) guideline at doses of 300 and 2000 mg/kg body weight. The combination with the best antioxidant activity was then formulated into capsules and evaluated for physical quality. Results: The total phenolic content of bajakah jie xue teng extract (47.499 mg GAE/g) was higher than that of kebiul seed extract (16.554 mg GAE/g). The antioxidant activity of kebiul seed extract and bajakah jie xue teng extract showed IC₅₀ values of 125.271 ppm and 86.036 ppm, respectively. The extract combination at a 1:3 ratio exhibited the best antioxidant activity with an IC₅₀ value of 36.434 ppm, which was superior to the 1:1 (78.371 ppm) and 3:1 (52.889 ppm) ratios. The acute toxicity test revealed no signs of toxicity or mortality up to a dose of 2000 mg/kg BW, classifying the combination as Category 5 (unclassified) with an estimated LD₅₀ > 2000 mg/kg BW. The capsule formulation met the physical quality requirements, with granule moisture content of 6.13%, an angle of repose of 24°, weight uniformity within the specified limits, and a disintegration time of 11 minutes and 12 seconds. Conclusion: The combination of kebiul seed and bajakah jie xue teng extracts at a 1:3 ratio demonstrated higher antioxidant activity than the single extracts, exhibited a very low acute toxicity profile, and was successfully formulated into capsules with good physical quality. This combination holds promise for development as an effective and safe natural antioxidant source.